Model of an acoustic source with discontinuous optimal elements - A. BRAŃSKI (Archives of Acoustics)
A new multi-elements model is considered. This model is composed of a sequence of discontinuous elements. They are constructed basing on the zeros of the Tchebycheff's polynomial. In this case, the discontinuous elements, and consequently the discontinuous model, are obtained. Such a model is particularly useful for modelling a source with corners and arbitrary boundary conditions. It has been proved that the new model is of better quality than other ones applied in the BEM up to now. To confirm this conclusion, the error of the new model and their acoustic fields have been compared with those of different other models. In order to clearly demonstrate the advantages of the new model, a plane and fully axisymmetric source has been taken into account, however the idea of the model with discontinuous elements can be applied to more practical problems.